Nonlinear fem analysis of cement column configuration in the foundation improved by deep mixing method - Nguyen Ngoc Thang; Nguyen Anh Tuan (КНУБА, 2018)
In this study, the stress distribution and the deformation in the foundation improved by Deep Mixing Method are analyzed using nonlinear FEM in which the stress-strain relation is elastoplastic to apply to more detailed specification of the configuration of cement column.
Keywords: Deep Mixing Method; soft soil; cement column; FEM; Simplified Method; 624.138.23(597)